Performance Comparison of GaN HEMTs on Diamond and SiC Substrates Based on Surface Potential Model. (1st January 2017) - Wu, Qingzhi; Xu, Yuehang; Zhou, Jianjun; Kong, Yuechan; Chen, Tangsheng; Wang, Yan; Lin, Fujiang; Fu, Yu; Jia, Yonghao; Zhao, Xiaodong; Yan, Bo; Xu, Ruimin
Abstract : In this paper, the performance difference of AlGaN/GaN high-electron mobility transistors (HEMTs) with same epitaxial structure fabricated silicon carbide (SiC) and transferred to diamond substrate is examined based on the surface-potential (SP) model. The thermal resistances of these devices are extracted through finite element method (FEM) thermal analysis. Results show that GaN-on-diamond device has a lower thermal resistance than conventional GaN-on-SiC device, which demonstrates the thermal performance improvement of GaN-on-Diamond technology. By embedding thermal characteristic into carrier mobility in the conventional SP model, the effectiveness of model is validated through good agreement between simulation and measurements of DC and RF performance. Additionally, large-signal performance (output power Pout, power added efficiency PAE and Gain) on these two similar devices are compared under identical bias and temperature conditions based on the improved SP model, making this work be effective for improving the process of GaN-on-Diamond HEMTs.